2021
DOI: 10.1016/j.xcrm.2021.100205
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis shows that adipose tissue of persons with both HIV and diabetes is enriched for clonal, cytotoxic, and CMV-specific CD4+ T cells

Abstract: Highlights d Adipose tissue memory CD4 + T cells are frequently CD69 + in persons with diabetes d Persons with HIV and diabetes have more CX3CR1 + GPR56 + CD57 + (C-G-C +) CD4 + T cells d Adipose tissue C-G-C + CD4 + T cells and CD69 + CD4 + T cells are clonally expanded d C-G-C + CD4 + T cells are often CMV specific and have more inflammatory transcriptomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 91 publications
1
32
0
Order By: Relevance
“…We have previously shown that in diabetic PWH, but not diabetic HIV-negative individuals, adipose tissue is enriched for CD4 + T EM and T EMRA cells co-expressing CX3CR1, GPR56, and CD57 (Wanjalla et al, 2021). We assessed CD4 + and CD8 + T cells separately to evaluate the T cell compartment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that in diabetic PWH, but not diabetic HIV-negative individuals, adipose tissue is enriched for CD4 + T EM and T EMRA cells co-expressing CX3CR1, GPR56, and CD57 (Wanjalla et al, 2021). We assessed CD4 + and CD8 + T cells separately to evaluate the T cell compartment.…”
Section: Resultsmentioning
confidence: 99%
“…While there was a global increase in T cells, the overall distribution of T cell subsets was relatively conserved between diabetic PWH and diabetic HIV-negative persons. We could not resolve CX3CR1 or GPR56 expression to identify CD4 + CX3CR1 + GPR56 + CD57 + cells that have previously been associated with glucose intolerance in PWH (Wanjalla et al, 2021). However, the majority of these cells are likely contained within the CD4 + T EM and T EMRA populations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Sample preparation (RNA extraction, library preparation) and sequencing was performed at the Institute for Immunology and Infectious Diseases (Murdoch University, Perth, Western Australia) using the method described in Wanjalla et al 2021 [ 27 ], which is an adapted version of the SMARTseq2 and MARS-seq approaches [ 28 , 29 ]. Briefly, the assay utilized uniquely tagged primers for reverse transcription and template switching with a pre-amplification step to increase the yield and transcript length of the single-cell cDNA library.…”
Section: Methodsmentioning
confidence: 99%